Recent Advances Of Silicon, Carbon Composites And Tin Oxide As New Anode Materials For Lithium-Ion Battery: A Comprehensive Review - Mohd Abid, Mohd Asyadi Azam; Ahmad, Aina Syuhada; Yuza, Nor Aqilah; Zulkifli, Nor Syazana Adilah; Safie, Nur Ezyanie (Elsevier Ltd, 2021)
Lithium-ion battery (LIB) is one of the most well-known types of batteries for portable electronics with low selfdischarge and high energy density and bettering pure lithium based batteries. The performance of the batteries is mainly influenced by efficient electrochemical redox reactions between anode and cathode. Good anode materials properties will enhance the performance of the LIBs. New materials such as silicon, carbon composites and tin oxide based anode have been studied as the potential substitute to the most common anode material, graphite. Furthermore, these anode materials were analysed to identify their impact to the performance of the LIBs. This review discussed the very recent (5 years) progress of the anode materials in LIBs compiling literatures from year 2016 to 2020. The overview on design (structures), recent developments and challenges of the new anode materials are presented in this review with considerations on their electrochemical performance in LIBs